Selection of optimal numerical method for implementation of Lorenz Chaotic system on FPGA - Karakaya, Barış; Türk, Meral Akarçay; Türk, Mustafa; Gülten, Arif (My University, 2018)
In this study, implementation of Lorenz chaotic system on Spartan 3e XC3S1600e FPGAdevelopment board by using Xilinx System Generator technology is presented. Differentialequations of any nonlinear system have to be discretized before coding and design process onFPGA editor. The Lorenz chaotic system is discretized by using Taylor series expansion, RungeKutta and Euler discretization methods which are mostly preferred to discretize the continuousformed signals. The optimal numerical method based on application area is proposed by provingaccuracy and complexity of methods and comparing designs in terms of resource utilizations onFPGA board.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği